Family and social class differences in sports behavior motivation among college students: An empirical study based on the latent class model - Liu, Liping; Chen, Shanping; Yang, Xueyan; Yang, Yuqing (Frontiers in Psychology, 2023)
Objective This article aims to explore the potential categories of college students’ sports behavior motivation and the differences between different family social classes on potential categories. Participants In total, 1,092 college students were investigated in this study. Methods This article used the “College Students’ Sports Behavior Motivation Questionnaire” to survey 1,092 college students using the whole group sampling method. The potential profile analysis method was applied to classify the types of college students’ sports behavior motivation and further analyze the characteristics of different family social classes and sports behavior motivation. Results College students’ sports behavior motivation types can be divided into the following four categories: “low motivation type” (0.82%), “healthy appearance type” (11.45%), “healthy fun type” (37.36%), and “high motivation type” (50.37%). The higher the family’s social class, the more the sports behavior motivation of college students tends to be healthy appearance, health, fun, and high motivation. The lower the family social class, the more motivational sports behavior of college students tends to be low motivation. The better the perception of health, the higher the probability that college students belong to the high-motivation type. The fewer chronic diseases that college students have are associated with a healthy appearance and high motivation. Conclusion There is a certain relationship between the type of college students’ sports behavior motivation and their family social class. Therefore, in school physical education, we should open all kinds of sports activities according to college students’ sports behavior motivation needs and focus on college students with lower family social class in order to intervene precisely on their motivation for sports behaviors, improve participation, and promote the overall health of college students.